Geochronology and glass geochemistry of major Pleistocene eruptions in the Main Ethiopian Rift: Towards a regional tephrostratigraphy. (15th August 2022) - Vidal, Céline M.; Fontijn, Karen; Lane, Christine S.; Asrat, Asfawossen; Barfod, Dan; Tomlinson, Emma L.; Piermattei, Alma; Hutchison, William; Tadesse, Amdemichael Zafu; Yirgu, Gezahegn; Deino, Alan; Moussallam, Yves; et al.
Abstract: The Main Ethiopian Rift (MER) is renowned as a focus of investigations into human origins. It is also the site of many large volcanic calderas, whose eruptions have spanned the timeframe of speciation, cultural innovation, and dispersal of our species. Yet, despite their significance for dating human fossils and cultural materials, the timing and geochemical signatures of some of the largest eruptions have remained poorly constrained at best. Here, through a programme of field surveys, geochemical analysis and 40 Ar/ 39 Ar dating, we report the ages of MER ignimbrites and link them to widespread tephra layers found in sequences of archaeological and paleoenvironmental significance. We date major eruptions of Fentale (76 ± 18 ka), Shala (ca. 145–155 ka), Kone (184 ± 42 ka and ca. 200 ± 12 ka) and Gedemsa (251 ± 47 ka) volcanoes, and correlate a suite of regionally important tephra horizons. Geochemical analysis highlights the predominantly peralkaline rhyolitic melt compositions (7.5–12 wt% Na2 O + K2 O, 70–76 wt% SiO2 ) across the central MER and remarkable similarity in incompatible trace element ratios, limiting the correlation of deposits via glass composition alone. However, by integrating stratigraphic and geochronological evidence from proximal deposits, lake sediment cores and distal outcrops at archaeological sites, we have traced ash layers associated with the ca. 177 ka Corbetti, ca. 145–155 ka Shala and ca. 108 ka Bora-Baricha-Tullu-Moye eruptions across southern Ethiopia. In addition to strengthening the tephrochronological framework that supports paleoenvironmental and archaeological work in the region, our findings have wider implications for evaluating the hypothesis of a middle Pleistocene 'ignimbrite flare-up' in the MER, and for evaluating the impacts of these great eruptions on landscapes, hydrology, and human ecology. Highlights: Quaternary explosive eruptions in the Main Ethiopian Rift linked to palaeoanthropological and archaeological archives. Review of the Pleistocene calderas of Main Ethiopian Rift. An improved middle to late Pleistocene tephrostratigraphy for the Ethiopian Rift.